الأحوال الاجتماعية في بنجلاديش وتأثيراتها في المراهقين إيجابًا وسلبًا خلُقياً = Social condition in Bangladesh and its positive and negative impact among teenagers in terms of morality - Hasan, Mohamed Nazmul; Mohammed Yaqub, Mohammed Abullais Shamsuddin (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia., 2018)
يهدف هذا البحث إلى إبراز الأحوال الاجتماعية لدولة بنجلاديش وتأثيراتها على المراهقين والمراهقات من الناحية الخُلقية والقيمية، وكما هو معروف أن المجتمع له دور كبير في التنمية الخلقية سواء كان صغيرًا أمْ كبيرًا، وأن التغيير مشهود عبر الزمان والمكان، إذا كانت أحوال المجتمع صالحة طيبة فيستفيد بها الجميع، وإنْ كانت سيئة فيتضرر بها الجميع، وتظهر أهمية هذه الدراسة في أنها تكشف الأحوال الاجتماعية وسطوتها على المراهقين والمراهقات كي يصونوا أنفسهم من العواقب السيئة، واتبعت هذه الدراسة المنهج التحليلي لبيان الأحوال الاجتماعية بشيء من التفصيل. ********************************************************* This research aims to bring out social condition of Bangladesh and its influence on teenagers in terms of morality. It is well-known that society has important role upon children, teenagers, and adults respectively. If the social condition is good, then everybody gets benefit from the society and vice-versa. In this study, the researcher will focus on teenagers regarding the morality because they have been impacted by society positively and negatively. However, Bangladesh is very small country but its population is huge. Teenagers are the part of this mass population and they are future of the country. They should be encouraged to hold positive part of the society as well as discouraged to avoid negative side of it. Hence, they can restraint themselves from bad difficulties of society. The researcher will follow an analytical approach to explain social condition of Bangladesh.